2008
DOI: 10.1007/s00284-008-9275-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Legionella pneumophila in the Viable But Nonculturable State After Monochloramine Treatment

Abstract: Legionella pneumophila, a facultative intracellular human pathogen, can persist for long periods in natural and artificial aquatic environments. Eradication of this bacterium from plumbing systems is often difficult. We tested L. pneumophila survival after monochloramine treatment. Survival was monitored using the BacLight Bacterial Viability Kit (Molecular Probes), ChemChrome V6 Kit (Chemunex), quantitative polymerase chain reaction and culturability on buffered charcoal-yeast extract agar. In nonculturable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 24 publications
0
88
0
Order By: Relevance
“…Two potential remedies for the low PPV with samples from environmental sources include reverse transcription-PCR, amplifying labile RNA targets present in metabolically active bacteria, and the use of a cell-impermeant chemical, such as ethidium monoazide (EMA) or propidium monoazide (PMA), to inhibit PCR amplification from nonviable cells or extracellular nucleic acids (385)(386)(387)(388)(389)(390). Notably, neither alternative protocol alone will discriminate VBNC legionellae; however, this cell population still poses a potential human health risk (391)(392)(393)(394).…”
Section: Nucleic Acid-based Molecular Diagnosticsmentioning
confidence: 99%
“…Two potential remedies for the low PPV with samples from environmental sources include reverse transcription-PCR, amplifying labile RNA targets present in metabolically active bacteria, and the use of a cell-impermeant chemical, such as ethidium monoazide (EMA) or propidium monoazide (PMA), to inhibit PCR amplification from nonviable cells or extracellular nucleic acids (385)(386)(387)(388)(389)(390). Notably, neither alternative protocol alone will discriminate VBNC legionellae; however, this cell population still poses a potential human health risk (391)(392)(393)(394).…”
Section: Nucleic Acid-based Molecular Diagnosticsmentioning
confidence: 99%
“…It has been shown that unculturable L. pneumophila may resuscitate to a fully virulent form by passage through an amoebal host (30,33,34,36) and therefore provide a largely undetected source of infections. Unculturable Legionellae have been observed for example after prolonged incubation in laboratory tap water microcosms at different temperatures, including elevated temperature at 42°C (36), heat shock (50 -70°C) (37), following disinfection (31)(32)(33), and after treatment with heavy metals (38).…”
mentioning
confidence: 99%
“…In fact, surfaceadherent microorganisms and bacteria living in protozoa are unrecognized by conventional methods (8). Alleron et al (2) have studied the effect of monochloramine on Legionella pneumophila and demonstrated that this bacterium can persist for long periods in biofilms in the VBNC state.…”
mentioning
confidence: 99%